Bird-of-Paradise - Sydney Park Brown; Robert J. Black (EDIS)
Revised! ENH-79, a 3-page illustrated fact sheet by Sydney Park Brown and Robert J. Black, has been updated throughout. Includes description, related species, planting and care, propagation, and pest and disease problems. Published by the UF Department of Environmental Horticulture, July 2007.